#TITLE_ALTERNATIVE# - AMSYAH (NIM : 10308024); Dosen Pembimbing : Dr. Kiki Vierdayanti, ANWAR
Ultraluminous X-ray sources (ULXs) are X-ray sources with x-ray luminosity between 1039 to 1041 erg / s within 0.3 to 10 keV. Off-side location of these sources from the optical center of the galaxy (off-nuclear), distinguish the objects from Active Galactic Nuclei (AGNs). ULXs spectrum is in general quite similar to that of black hole binaries (BHBs) spectrum, yet no conclusive models for ULXs, hitherto, due to the lack of observational data for dinamycal mass estimation. There are two plausible models for ULXs, i.e stellar mass black holes (StMBHs) and intermediate mass black holes (IMBHs) model. In ters of their population, ULXs reside at almost all morphological types of galaxies. Apparently, the spiral galaxies possess most ULXs. However, it doesn't imply that ULXs distribution peaks at this type of galaxies, since more spiral galaxies are indeed observed in a certain distance. Approximately 668 of the reported ULXs were found in 226 galaxies, resulting on average, about 3 ULXs/galaxy. Among 668 ULXs mentioned above, 439 ULXs Ade obtained from the Study of Scientifiec articles/references which is one of the goals of this thesis. . More ULXs are occupying interacting galaxies with average number density over 5 ULXs/interacting-galaxy. Example of this case is interacting galaxy M51 which has 9 ULXs. SWIFT si is one of many X-ray satellite which provides quite mount of ULXs data. Furthermore, its ability to do monitoring observation distiguished it with other x-ray satellite in terms of ULXs studies. Data reduction is carried out using HEASoft. From study of 9 ULXs in M51, in general Kwe Finn on significant variability in their intensity, except for ULX 3 whole luminositas changes about a factor of during the observation.